2009
DOI: 10.1111/j.1538-7836.2009.03465.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of PF4/heparin immunoassays for the diagnosis of heparin-induced thrombocytopenia

Abstract: Our observation indicates that an IgG-ELISA provides the best diagnostic information of all antigen-binding assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 29 publications
6
114
0
1
Order By: Relevance
“…24,25 However, simply increasing the cut-off of the OD value to improve diagnostic specificity invariably compromises the sensitivity and leads to unacceptable numbers of false-negatives. 26,27 The use of a high heparin "confirmatory" step is yet another serologic parameter that has been investigated for improving assay specificity. Because HIT antibodies show heparindependent binding, the addition of excess heparin (2-100 U/mL) competes and/or disrupts binding of HIT antibodies to pre-formed PF4/H complexes.…”
mentioning
confidence: 99%
“…24,25 However, simply increasing the cut-off of the OD value to improve diagnostic specificity invariably compromises the sensitivity and leads to unacceptable numbers of false-negatives. 26,27 The use of a high heparin "confirmatory" step is yet another serologic parameter that has been investigated for improving assay specificity. Because HIT antibodies show heparindependent binding, the addition of excess heparin (2-100 U/mL) competes and/or disrupts binding of HIT antibodies to pre-formed PF4/H complexes.…”
mentioning
confidence: 99%
“…This method has been applied to the detection of a broad spectrum of antibodies ranging from those against Helicobacter pylori 7 to markers in rheumatoid arthritis, 8,9 lupus 10 and heparin-induced thrombosis. 11 Other related fluorescent marker approaches include, for example, immunoprecipitation assays and recombinant immunofluorescence assays for detection of antibodies to aquaporin-4 in patients with neuromyelitis optica. 12,13 Increasingly, these sensing techniques are being developed as antigen-bound micro-arrays in which large numbers of antigens are anchored to a substrate to show good sensitivity and low detection limit due to a high fluorescence signal, or a combination of antigens are bound providing a multiparametric sensor for a range of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity was higher for the IgG-specific EIA (89% versus 81%), and could be further increased by increasing the OD cutoff at the expense of sensitivity, as would be anticipated. The authors found that a cutoff OD of 0.65 reflected the optimal compromise between sensitivity and specificity (sensitivity 97.1% and specificity 92.4%) [42]. This cutoff cannot be universally applied, however, as OD thresholds vary between laboratories.…”
Section: Laboratory Detection Of Hit Antibodiesmentioning
confidence: 99%
“…In the aforementioned study by Bakchoul et al [42], the authors included PaGIA in their evaluation of different antigen binding assays. The PaGIA had a PPV of 36.6%, compared with 28% for Poly-EIA and 40.6% for IgG-specific EIA.…”
Section: Laboratory Detection Of Hit Antibodiesmentioning
confidence: 99%